Communication system for controlling smart appliances using power line communication - Khan S.; Islam R.; Khalifa O.O.; Omar J.; Hassan A.; Adam I. (Institute of Electrical and Electronics Engineers Inc., 2023)
Microcontroller-based master and slave units are designed with serial ports for communication with a computer and a transmission port to couple the signal to modems at both ends. The programming of the microcontrollers at either end for formatting the data bits before they are sent down the power line and the development of software for putting in place the required master and slave protocols is presented. Coupling data signals to power line through interfacing circuits is a challenging task as power line and the communication system operate at two extremes - very low frequency and high power for the power line while communication is working at very high frequency and very low voltage and current levels. Hence, the coupling circuit to be designed must be capable to withstand the high power system side in order to prevent a damage being done to the electronic side of the communication system. At the same time it must be reliable enough to make sure that data bits are transferred on to the power line with high accuracy. The interfacing circuits are designed and tuned to frequency contents making the bits of data. The frequency performance of these coupling circuits is presented, showing the range a power line can be used for communication of such data. 2006 IEEE.